EXISTING PRACTICE OF WRITTEN AND UNWRITTEN CURRICULUMS AND THEIR IMPACT ON STUDENTS IN COMMUNITY SCHOOLS IN NEPAL - Acharya, Bisna; Sigdel, Surya (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2024)
This study aims to examine the existing implementation of curriculum in school education, including explicit, covert, and null-curriculum aspects. This has been conducted in the community schools of Kathmandu to examine the factors contributing to the difference between the expected learning outcomes of school education and the actual results as stated in the curriculum. The study involved grade-eight students and their teachers from five community schools situated in the suburban suburbs of Kathmandu. The authors used a range of data collection techniques, including thorough interviews, group discussions, and direct observation. The study found that educational activities that encourage students to create meaningful connections are more valuable than those that discourage them from gaining real-world knowledge and skills. The curriculum promotes educational activities that actively engage learners and are guided by teachers. This approach helps students develop the necessary academic and transversal competencies. To cultivate students with the necessary skills, it is crucial for the curriculum to address the adverse effects of inadequate teaching and the overemphasis on high-stakes testing. This has resulted in a disproportionate emphasis on exam-focused instruction and learning. The study suggests that the curriculum should integrate the essential elements of the written, hidden, and null curriculum to provide hands-on learning experiences and promote the growth of both academic and transferable skills in children.